\(^x\) + 2\(^{x+1}\) + 2\(...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 6 2017

\(2^x+2^{x+1}+2^{x+2}+2^{x+3}=120\)

\(\Rightarrow2^x+2^x\cdot2+2^x\cdot4+2^x\cdot8=120\)

\(\Rightarrow\left(1+2+4+8\right)\cdot2^x=120\)

\(\Rightarrow15\cdot2^x=120\)

\(\Rightarrow2^x=\dfrac{120}{15}=8=2^3\)

\(\Rightarrow x=3\)

Vậy............

27 tháng 6 2017

\(2^x+2^{x+1}+2^{x+2}+2^{x+3}=120\)

\(=2^x.1+2^x.2^1+2^x.2^2+2^x.2^3=120\)

\(=2^x.1+2^x.2+2^x.4+2^x.8=120\)

\(=2^x\left(1+2+4+8\right)=120\)

\(=2^x.15=120\)

\(2^x=120:15=8\)

\(2^x=2^3\Leftrightarrow x=3\)

17 tháng 8 2018

a,(=)\(3^{x+1}.\left(3+4\right)=7.3^6\)

(=)\(3^{x+1}=3^6\)

=>x+1=6(=)x=5

b

1 tháng 2 2024

Lalalalalalalalalalalalalalalala

2 tháng 8 2016

a)\(\frac{1}{4}-\frac{1}{3}x=\frac{2}{5}-\frac{3}{2}x\)

\(\Leftrightarrow\)\(\frac{15-20x}{60}=\frac{24-90x}{60}\)

\(\Leftrightarrow15-20x=24-90x\)

\(\Leftrightarrow-20x+90x=24-15\)

\(\Leftrightarrow70x=9\)

\(\Leftrightarrow x=\frac{9}{70}\)

 

c) (1/2-1/6)*3^x+4-4*3^x=3^16-4*3^13

=1/3*3^x*3^4-4*3^x=3^13*3^3-4*3^13

=27*3^x-4*3^x=3^13*(27-4)

=3^x*(27-4)=3^13*(27-4)

=>x=13

16 tháng 9 2017

Ta có : \(\frac{\left(4^x\right)^2}{2^x}=8\)

\(\Rightarrow4^{2x}=8.2^x\)

\(\Rightarrow4^{2x}=2^3.2^x\)

\(\Rightarrow\left(2^2\right)^{2x}=2^{x+3}\)

\(\Rightarrow2^{4x}=2^{x+3}\)

=> 4x = x + 3

=> 3x = 3

=> x = 1

Vậy x = 1. 

13 tháng 8 2018

1/ 2x = 45.46

=> 2x = 45 + 6

=> 2x = 411

=> 2x = (22)11

=> 2x = 222

=> x = 22

vậy_

2/ 2x = 46.163

=> 2x = (22)6.(24)3

=> 2x = 212.212

=> 2x = 212 + 12

=> 2x = 224

=> x = 24

3/ 2x = 45.162

=> 2x = (22)5.(24)2

=> 2x = 210.28

=> 2x = 210 + 8

=> 2x = 218

=> x = 18

vậy_

13 tháng 8 2018

\(\frac{1}{2^x}=4^5.4^3=4^{5+3}=4^8\)

\(\Rightarrow1=4^8.2^x=2^{2.8+x}=2^{16+x}\)

ta có 1 < 21 =>  216+x < 21

=> 216+x = 20

=> 16+x=0

=> x= -16

2 tháng 9 2019

56++8HJK

2 tháng 9 2019

a.

X/3 = - 3/Y

=> XY = - 9

=> X = {-9; - 3; - 1; 1; 3 ; 9} <=> Y = {1; 3 ; 9; - 9; - 3;-1}

11 tháng 10 2016

a) \(\frac{x-3}{x+5}=\frac{5}{7}\)

\(\Rightarrow\left(x-3\right).7=\left(x+5\right).5\)

\(\Rightarrow7x-21=5x+25\)

\(\Rightarrow7x-5x=21+25\)

\(\Rightarrow2x=46\)

\(\Rightarrow x=23\)

Vậy \(x=23\)

11 tháng 10 2016

b) \(\frac{7}{x-1}=\frac{x+1}{9}\)

\(\Rightarrow\left(x-1\right).\left(x+1\right)=7.9\)

\(\Rightarrow\left(x-1\right)x-\left(x+1\right)=7.9\)

\(\Rightarrow x^2-x-x-1=63\)

\(\Rightarrow x^2-1=63\)

\(\Rightarrow x^2=64\)

\(\Rightarrow x=8\) hoặc \(x=-8\)

Vậy \(x=8\) hoặc \(x=-8\)

c) \(\frac{x+4}{20}=\frac{5}{x+4}\)

\(\Rightarrow\left(x+4\right)^2=100\)

\(\Rightarrow x+4=\pm10\)

+) \(x+4=10\Rightarrow x=6\)

+) \(x+4=-10\Rightarrow x=-16\)

Vậy \(x\in\left\{6;-16\right\}\)